A low-cost mixed fullerene acceptor blend for printed electronics. Issue 26 (16th June 2016) - Cooling, N. A.; Barnes, E. F.; Almyahi, F.; Feron, K.; Al-Mudhaffer, M. F.; Al-Ahmad, A.; Vaughan, B.; Andersen, T. R.; Griffith, M. J.; Hart, A. S.; Lyons, A. G.; Belcher, W. J.; et al.
Abstract : The synthesis and performance of a cost-effective mixed fullerene at the 100+ g scale with a reaction yield of 85% is demonstrated. Abstract : The synthesis and performance of a cost-effective mixed fullerene at the 100+ g scale with a reaction yield of 85% is demonstrated. The cost to convert a fullerene such as C60 into the mixed acceptor blend is less than $1 g −1 . The photovoltaic performance of the mixed acceptor is demonstrated in both small scale and roll-to-roll printed devices.